A Systematic Review of Patients’ Perspectives on the Subcutaneous Route of Medication Administration - Ridyard, Colin H.; Dawoud, Dalia M. M.; Tuersley, Lorna V.; Hughes, Dyfrig A. (The patient : patient-centered outcomes research, 2016)
Background Subcutaneous injections allow for self-administration, but consideration of patients’ perspectives on treatment choice is important to ensure adherence. Previous systematic reviews have been limited in their scope for assessing preferences in relation to other routes of administration. Objective Our objective was to examine patients’ perspectives on subcutaneously administered self-injectable medications when compared with other routes or methods of administration for the same medicines. Methods Nine electronic databases were searched for publications since 2000 using terms pertaining to methods of administration, choice behavior, and adverse effects. Eligibility for inclusion was determined through reference to specific criteria by two independent reviewers. Results were described narratively. Results Of the 1726 papers screened, 85 met the inclusion criteria. Studies were focused mainly on methods of insulin administration for diabetes but also included treatments for pediatric growth disorders, multiple sclerosis, HIV, and migraine. Pen devices and autoinjectors were favored over administration with needle and syringe, particularly with respect to ergonomics, convenience, and portability. Inhalation appeared to be more acceptable than subcutaneous injection (in the case of insulin), but how subcutaneous infusion, intramuscular injection, and needle-free injection devices compare with subcutaneous injections in terms of patient preference is less certain. Conclusions The review identified a number of studies showing the importance of the methods and routes of drug delivery on patient choice. However, studies were prone to bias, and further robust evidence based on methodologically sound approaches is required to demonstrate how patient choice might translate to improved adherence.